Introducing comprehensive multiphase NMR for the analysis of food: Understanding the hydrothermal treatment of starch-based foods. (15th December 2022) - Barison, Andersson; Biswas, Rajshree Ghosh; Ning, Paris; Kock, Flávio Vinícius Crizóstomo; Soong, Ronald; Di Medeiros, Maria Carolina Bezerra; Simpson, Andre; Lião, Luciano Morais
Graphical abstract: Highlights: CMP-NMR is introduced for food research. CMP-NMR allows all phases (solids, gels, liquids) to be monitored. 1 H and 13 C CMP-NMR spectra allows molecular fluxes to be studied. Spectral editing emphasized components from specific phases. Lipids are dominant mobile components in the uncooked foods. Starches gelatinize with cooking and structural water is mobilized. Abstract: Cooking is essential for preparing starch-based food, however thermal treatment promotes the complexation of biopolymers, impacting their final properties. Comprehensive Multiphase (CMP) NMR allows all phases (liquids, gels, and solids) to be differentiated and monitored within intact samples. This study acts as a proof-of-principle to introduce CMP-NMR to food research and demonstrate its application to monitor the various phases in spaghetti, black turtle beans, and white long-grain rice, and how they change during the cooking process. When uncooked, only a small fraction of lipids and structurally bound water show any molecular mobility. Once cooked, little "crystalline solid" material is left, and all components exhibit increased molecular dynamics. Upon cooking, the solid-like components in spaghetti contains signals consistent with cellulose that were buried beneath the starches in the uncooked product. Thus, CMP-NMR holds potential for the study of food and related processes involving phase changes such as growth, manufacturing, and composting.